Persepsi IKM 5 Tentang Penggunaan Media Sosial Dalam Edukasi Kesehatan - Andini Suci Rahmah; Khairin Nazwa; Shafira Putri Cantika (PT. Alahyan Publisher Sukabumi, 2025)
The purpose of this study is to investigate the role of social media in health education and its impact on changes in public health behavior. In the era of globalization and the advancement of information technology, social media has become a powerful tool to spread health information quickly and widely. To find out more about their thoughts on the use of social media in health education, students from IKM 5 Faculty of Public Health (FKM) took part in this qualitative descriptive study. According to the interviews, social media sites such as Instagram, Twitter, TikTok, and YouTube are considered helpful for spreading the latest health information, but they can also cause problems by containing false information that can mislead the public. Female students stated that they prefer to get health information from leading medical experts and underlined the importance of creating engaging and understandable content. Social media has the ability to influence lifestyle and health decisions because it has a lot of content that promotes healthy living. However, if the information disseminated is wrong, there can be detrimental effects. The study came to the conclusion that while social media can be a useful tool for promoting health, it should be used with caution to prevent the spread of false information. Therefore, to optimize the advantages of social media in health education, a plan is needed to improve digital literacy.